Realism and sociology : anti-foundationalism, ontology, and social research - Cruickshank, Justin, 1969- (Routledge studies in critical realism, 2003)
In recent years, methodology debates in the social sciences have increasingly focused on issues relating to epistemology. Realism and Sociology makes an original contribution to the debate.